Pedagogical supervision as a collaborative process of vocational training - Sanches, Angelina (2018)
In this paper we will discuss the role of pedagogical supervision in the initial training of early childhood educators/teachers. Supervision is understood as the process that supports and regulates the learning and professional development, which forms part of a social constructivist and ecological approach. The importance of embarking on a reflexive (inter)action committed to the construction of quality educational and training responses is emphasized. Worth noticing are also the contributions of the different actors and institutional contexts in the creation of a supervising environment that could facilitate their learning and professional development.